Digital Law Journal: Introduction - M. I. Inozemtsev (Цифровое право)
Dear Readers, I am glad to greet you in the pages of the international, peer-reviewed Digital Law Journal. The mission of the Journal is to provide a platform to exchange and discuss information around various research aspects and best practices concerned with the legalization of digital technologies. Another fundamental goal is to elucidate the peculiarities of these technologies and their implementation prospects within a legal and regulatory framework.